Pengaruh Perputaran Kas, Non Performing Loan (NPL) dan BOPO terhadap Likuiditas pada Perusahaan Perbankan Swasta yang Terdaftar di Bei - Indra Ramadhan; Nafisah Nurulrahmatiah; Aris Munandar (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
The Indonesian banking industry faces complex challenges in managing liquidity, particularly among national private banks. This research analyzes the effect of cash turnover, Non-Performing Loans (NPL), and Operational Costs to Operating Income (BOPO) on the liquidity of private banks listed on the Indonesia Stock Exchange (IDX) during 2020–2023. Secondary data were collected from annual financial reports and analyzed using multiple linear regression. The results indicate that cash turnover, NPL, and BOPO have no significant impact, either partially or simultaneously, on liquidity. These findings suggest that bank liquidity is more strongly influenced by external factors such as monetary policy, macroeconomic conditions, and customer behavior. The study provides implications for bank management to develop adaptive liquidity management strategies based on macroeconomic analysis to maintain financial stability amid market dynamics.